Nyarik Kopi di Tabanan Bali: Estetika, Otentisitas, dan Digital Engagement sebagai Daya Tarik Wisata Modern - Randhi Nanang Darmawan; Saroh Fitriani (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
This study examines the phenomenon of Nyarik Kopi as a culinary tourism attraction that serves as a modern tourism destination rooted in local aesthetics and authenticity in Tabanan, Bali. By combining the natural beauty of rural landscapes—rice fields, mountains, and clear irrigation streams—with an innovative business concept using modified classic motorcycles, Nyarik Kopi offers a unique and authentic tourism experience. This research employs a descriptive qualitative method through field studies, in-depth interviews, and social media analysis to identify its strengths, the role of digital engagement, and operational challenges. The findings indicate that local aesthetics and authenticity are the main attractions, while the innovative business concept strengthens the brand identity and enhances competitiveness. Digital engagement, particularly through Instagram, plays a crucial role in promotion, building digital communities, and expanding market reach. Meanwhile, operational challenges, such as dependency on weather conditions and logistical limitations, can be addressed through adaptive strategies, including operational flexibility and a pre-order system. This study concludes that the synergy between local aesthetics, business innovation, digital technology, and operational management can serve as a model for sustainable creative tourism development. These findings contribute to the modern tourism literature and provide strategic insights for similar ventures in experience-based tourism.